Pyrolysis of Golden Snail Shells (Pomacea canaliculata L.) for Phosphorus Removal from Aqueous Solutions - M. T. Vu; L. Hoang; M. Dao (Chemical and Biochemical Engineering Quarterly)
Biochar derived from abundant waste biomass has emerged as an eco-friendly alternative to conventional adsorbents. In this study, biochar produced from golden snail shells through a simple pyrolysis process was applied for phosphorus adsorption. The effects of pyrolysis temperature and time on adsorption capacity were investigated. The biochar pyrolyzed at 800 °C for 90 min (B800) exhibited the best adsorption performance. Optimal adsorption conditions were determined to be a pH of 4.0 and an adsorbent dose of 1.6 g L–1. The adsorption of phosphorus onto B800 could be well described by the Langmuir model and the pseudo-first-order model, achieving a maximum adsorption capacity of 63.5 mg g–1 and a rate constant of 0.029 min–1. This study highlights the potential of biochar derived from agricultural waste as a highly efficient and environmentally friendly adsorbent for phosphorus removal. Furthermore, the adsorption mechanism, driven by the electrostatic interaction occurring prior to Ca-P precipitation, was elucidated. The phosphorus adsorbed onto biochar can potentially be recycled as a soil fertilizer.